The Role of the Work Environment and Organizational Communication in Increasing Work Morale and Job Satisfaction in Government Institutions - Alfianto, Andres Dwi; Musoli (The Indonesian Institute of Science and Technology Research, 2024)
In the face of intense global competition, job satisfaction plays a crucial role in employee productivity and retention, influenced by both individual and organizational factors such as the work environment and organizational communication. A supportive work environment and effective communication boost employee morale and positively impact job satisfaction. This study explores how the work environment and organizational communication contribute to job satisfaction, with work morale acting as a mediating variable, using data from 92 Government Institution Employee X respondents collected through a purposive sampling technique. A 5-point Likert scale questionnaire analyzed with SPSS 21 reveals that the work environment and organizational communication significantly influence work morale and job satisfaction, while work morale mediates their impact on job satisfaction. The findings suggest that the institution should prioritize fostering a supportive work environment and enhancing internal communication to improve employee morale and overall job satisfaction.